HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN IBU RUMAH TANGGA DALAM PENGGUNAAN BUMBU MASAK INSTAN DI KELURAHAN TANJUNG SARI KECAMATAN MEDAN SELAYANG KOTA MEDAN - rika rangkuti; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
The increasingly sophisticated technology and high consumerism attitude is closely associated with people's lives now. The information is very easily obtained from broadcast television and other mass media. The information gathered will influence public knowledge particularly housewives who spent much time watching television. Lifestyle with an increasing preoccupation causes housewife choose something more practical and faster in providing food in the household. The best option that is using the instant cooking spices because it is easy to get, cheap, and delicious taste. Instant cooking spices contain preservatives, food dyes, artificial sweeteners and MSG that can damage human health. The purpose of the study is to know the correlation of knowledge and attitudes with the practice of housewives in the use of the instant cooking spices in the village of Tanjung Sari Subdistrict Medan Selayang. The design of research is cross-sectional method. The population in this study is all the housewives in Tanjung Sari Subdistrict and the number of samples as many as 99 people who obtained by simple random sampling. Statistical tests used was Chi-Square. Results of research data obtained through interviews and questionnaires that include data filling the knowledge, the attitude and actions of the housewife in the use of instan cooking spices. The results of statistical tests show that the existence of a significant relationship between knowledge about instant cooking spices with the action of housewife (p < 0.05), as well as the attitude of housewife action against the use of instant cooking spices (p < 0.05). Knowledge and attitudes of the housewife about instant cooking spices that good has correlation with the practice of a housewife in the use of the instant Cook spices that good. Employees of the Neighborhood through the mothers PKK in cooperation with health agencies in order to promote public awareness about the negative effects of the use of the instant Cook seasoning products.